(untitled) (Perner’s Contacts, 2009)
The paper is focused on the project ERWIN, which is solved on University of Pardubice, Jan Perner Transport Faculty, Department of Transport Technology and Control. The project is focused on creation of software tool for data processing and graphic visualization of European railway infrastructure. One of the main functions of this tool is optimisation of railway freight transport based on the given criteria.